Kajian Penambahan Tepung Daun Kelor (Moringa oleifera L.) Pada Formulasi Flakes Dari Tepung Sagu (Metroxylon sagu) - Masrukan; Idra Faudu, Muhammad; Darmawan, Eman (Universitas Widya Mataram, 2025)
This study employed a Randomized Block Design (RBD) with five formulations of moringa flour (2.5%, 5%, 7.5%, 10%, and 12.5%), each repeated twice, resulting in a total of 10 experimental units. The analysis included both chemical tests (water content, ash content, fat content, texture, and flavonoid content) and organoleptic tests (aroma, color, taste, texture, and hedonic test). The results showed that the addition of moringa flour significantly affected the physical and chemical properties of the flakes.Flakes formulated with formula 5 (sago flour: moringa flour = 100:12.5) were identified as the best, based on the organoleptic test, with the highest overall liking score of 3.92. The chemical characteristics of Formula 5 flakes included a moisture content of 8.51%, an ash content of 1.35%, a fat content of 8.49%, a flavonoid content of 0.033%, and a texture score of 78.9%. In terms of sensory properties, Formula 5 flakes were preferred due to their distinctive yellowish-green color, flavor that subtly highlights the aroma of moringa, and crunchy texture.